The effectiveness of 13-valent pneumococcal vaccine against community acquired pneumonia in young children: a systematic review and meta-analysis - Ninel Revenco; Ana-Mihaela Balanuta; Dina Bujor; Adela Horodisteanu-Banuh; Olga Cirstea (Amaltea Medical Publishing House, 2022)
Objective. The present meta-analysis study aimed to evaluate the effectiveness of 13-valent pneumococcal conjugate vaccine (PCV) in reducing the morbidity from pneumonia among children under 5 years old. Material and methods. Cochrane and Medline electronic databases were systematically searched for studies reporting effectiveness of 13-valent pneumococcal conjugate vaccine against pneumonia among children of the foreseen age group. To assess the effect measure, we used the odds ratio (OR) with 95% confidence intervals (95% CI) for dichotomous outcomes. The heterogeneity of the studies was assessed using I2 and Chi2 statistics. Outcomes. The meta-analysis found a non-significant association between vaccinated children and the development of community-acquired pneumonia (OR=0.50; CI 95%: 0.44-0.57; Chi2=6.07; I2=18%). Vaccine effectiveness (VE) of 13-valent PCV was calculated as (1 - Mantel-Haenszel OR in vaccinated children compared to unvaccinated children) x100%. Thus, the VE of PCV 13 valent was estimated to be about 50%, according to the meta-analysis of the included studies. Conclusions. Our study showed that the group of vaccinated children experienced 50% fewer cases of pneumonia than they would have had if they had not been vaccinated. These data bring additional evidence that vaccination is an effective strategy to prevent community acquired pneumonia in young children.